Burns and Scalds Assessment Template: standardising clinical assessment of childhood burns in the emergency department. Issue 6 (22nd April 2020) - Hepburn, Kirsty; Bennett, Verity; Kemp, Alison Mary; Hollen, Linda Irene; Nuttall, Diane; Roberts, Zoe; Farrell, David; Mullen, Stephen
Abstract : Objectives: The Burns and Scalds Assessment Template (BaSAT) is an evidence-based proforma coproduced by researchers and ED staff with the aim of (1) standardising the assessment of children attending ED with a burn, (2) improving documentation and (3) screening for child maltreatment. This study aimed to test whether the BaSAT improved documentation of clinical, contributory and causal factors of children's burns. Methods: A retrospective before-and-after study compared the extent to which information was recorded for 37 data fields after the BaSAT was introduced in one paediatric ED. Pre-BaSAT, a convenience sample of 50 patient records of children who had a burn was obtained from the hospital electronic database of 2007. The post-BaSAT sample included 50 randomly selected case notes from 2016/2017 that were part of another research project. Fisher's exact test and Mann-Whitney U tests were conducted to test for statistical significance. Results: Pre-BaSAT, documentation of key data fields was poor. Post-BaSAT, this varied less between patients, and median completeness significantly (p<0.001) increased from 44% (IQR 4%–94%) to 96% (IQR 94%–100%). Information on 'screening for maltreatment, referrals to social care and outcome' was poorly recorded pre-BaSAT (median of 4% completed fields) and showed the greatest overall improvement (to 95%, p<0.001). Documentation of domestic violence at home and child's ethnicity improved significantly (p<0.001) post-BaSAT; however, these were still not recorded in 36% and 56% of cases, respectively. Conclusion: Introduction of the BaSAT significantly improved and standardised the key clinical data routinely recorded for children attending ED with a burn.